Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Using mathematical induction I would like to prove the following.


$S_1=1+a,...,S_n=\sum_{i=0}^n a^i$

Prove that $S_{n+1}=1+aS_n$ where $n \ge 0$.

share|cite|improve this question
What have you tried? What are you having difficulty with? This is straightforward. – Calvin Lin Feb 5 '13 at 6:35
up vote 3 down vote accepted

Check that it holds for $n=1$. Fix an $n\geq 1$ and assume that $S_n=\sum_{i=0}^n a^i$. $$ aS_n=a\sum_{i=0}^n a^i=\sum_{i=0}^n a^{i+1}=\sum_{i=1}^{n+1}a^i. $$ Now add $1$ and conclude that $S_{n+1}$ has the right form.

share|cite|improve this answer
Wow that was pretty simple. I get it now. When I first saw it I thought it would be much more difficult to solve it. Thanks. – Blue Pony Inc. Feb 5 '13 at 15:47

Hint $\ $ Below is an overview of the induction step.

$$\begin{eqnarray} \rm S_n =\, \sum_{i\, =\, 0}^n\,a^i\ \ \Rightarrow\ \ S_{n+1} &=&\rm\ \ S_n\ +\ a^n \\ \\ \rm Hence\ \quad S_{n+2} - a\, S_{n+1} &=&\rm\ (S_{n+1} +\color{#C00}{a^{n+2}}) - \color{#C00}a\,(S_{n}+\color{#C00}{a^{n+1}})\\ \\ &=&\rm\ \ S_{n+1} - a\, S_n\ =\ 1\ \ \ \text{by induction}\\ \end{eqnarray}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.